Vitamin D Status In Epileptic Adults With Valproic Acid Therapy At The Neurology Clinic, Diponegoro National Hospital, Semarang - Santoso Jaeri; Dwi Ngestiningsih; Hasna Syariva; Adelia Putri Maharani; Arinta Puspita Wati (Berkala Ilmiah Kedokteran Duta Wacana, 2021)
Background Epilepsy is a brain disease characterized by repeated unprovoked seizures at least two times with an interval of more than 24 hours between the first seizure and subsequent seizures. Valproic acid is an anti-seizure drug. Long-term use of valproic acid may be associated with metabolic disorders such as weight gain, and lipid profile changes, including vitamin D levels.Objectives To determine the correlation between the duration of valproic acid therapy and serum vitamin D levels in adults using valproic acid.Methods An observational analytic study with a cross-sectional design. The demographic and duration of valproic acid use were determined using questioner, and the serum vitamin D levels were measured using the ELISA method. The normality test was carried out using the Shapiro-Wilk test and then continued with the Pearson test to determine the correlation between the duration of valproic acid therapy and serum vitamin D levels. The results showed significance if the p-value <0.05.Results The mean serum vitamin D level among subjects was low (16.44+4,24 ng/mL), furthermore, there is no significant correlation between the duration of valproic acid therapy and serum vitamin D levels (p=0.956, r=-0,011).Conclusion There is vitamin D deficiency among adults with epilepsy but, the duration of valproic acid therapy does not correlate with serum vitamin D levels.